Left Main Coronary Artery Compression following Melody Pulmonary Valve Implantation: Use of Impella Support as Rescue Therapy and Perioperative Challenges with ECMO - Erica D. Wittwer; Juan N. Pulido; Shane M. Gillespie; Frank Cetta; Joseph A. Dearani (Case Reports in Critical Care)
The purpose of this case is to describe the complex perioperative management of a 30-year-old woman with congenital heart disease and multiple resternotomies presenting with pulmonary homograft dysfunction and evaluation for percutaneous pulmonary valve replacement. Transvenous, transcatheter Melody valve placement caused left main coronary artery occlusion and cardiogenic shock. An Impella ventricular assist device (VAD) provided rescue therapy during operating room transport for valve removal and pulmonary homograft replacement. ECMO support was required following surgery. Several days later during an attempted ECMO wean, her hemodynamics deteriorated abruptly. Transesophageal and epicardial echocardiography identified pulmonary graft obstruction, requiring homograft revision due to large thrombosis. This case illustrates a role for Impella VAD as bridge to definitive procedure after left coronary occlusion and describes management of complex perioperative ECMO support challenges.